Dakwah Digital Akademisi Dakwah - Muhaemin, Enjang (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2017)
Dakwah field in cyberspace requires the da'i, who in addition to the depth of Islamic science, broad insight kedakwahannya, also has the technical ability of internet usage is qualified. Researchers interested in studying how da'i academic da'i done in cyberspace. The subject of this research is the da'i of academics at Faculty of Da'wah and Communication UIN Bandung. The method used is descriptive analysis, which describes systematically facts or certain characteristics factually and meticulously. The theoretical perspective used is the theory of symbolic interaction. The results showed that the understanding of academicians to the internet as a medium of da'wah can be said relatively good enough. However, the level of mastery is relatively minimal, coupled with considerable obstacles resulted in low activity of academic da'i in utilizing the internet as da'wah. To improve effectiveness, integrated training is needed, availability of network access and adequate infrastructure, reward and punishmnet, exemplary, and the need to establish a separate institution with professional and forward-looking managers. Medan dakwah di dunia maya mensyaratkan para da’i, yang selain mendalam ilmu keislamannya, luas wawasan kedakwahannya, juga memiliki kemampuan teknis penggunaan internet yang mumpuni. Peneliti tertarik mengkaji bagaimana dakwah da’i akademisi dilakukan di jagat maya. Subyek penelitian ini adalah para da’i akademisi di Fakultas Dakwah dan Komunikasi UIN Bandung. Metode yang digunakan deskriptif analisis, yang melukiskan secara sistematis fakta atau karakteristik tertentu secara faktual dan cermat. Perspektif teoretis yang digunakan adalah teori interaksi simbolik. Hasil penelitian menunjukkan pemahaman da’i akademisi terhadap internet sebagai media dakwah dapat dikatakan relatif cukup baik. Namun, tingkat penguasaan yang relatif minim, ditambah dengan kendala yang cukup besar berakibat pada rendahnya aktivitas para da’i akademisi di dalam memanfaatkan internet sebagai dakwah. Untuk meningkatkan efektivitas, dibutuhkan pelatihan terpadu, ketersediaan akses jaringan dan infrastruktur memadai, pemberian reward dan punishmnet, adanya keteladanan, dan perlu dibentuknya lembaga tersendiri dengan pengelola yang profesional dan berwawasan ke depan.